2019
DOI: 10.1038/s41598-019-38828-9
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of placebo effects in sports: EEG frontal alpha asymmetry increases in response to a placebo ergogenic aid

Abstract: The performance enhancing (ergogenic) placebo effect is elicited by an inert treatment and caused by positive affective appraisal of effort perception. Frontal alpha asymmetry (FAA) is a neurobiological correlate of positive affect. This study investigates, whether receiving an ergogenic placebo increases FAA and whether scores on the behavioral inhibition and activation system (BIS/BAS) scales affect this increase in FAA. Nineteen competitive male cyclists (37.26 ± 9.82 years) performed two maximum effort tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
1
14
0
1
Order By: Relevance
“…Second, in line with previous findings suggesting that placebo improvement is underpinned by brain circuitry supporting reward and valuation mechanisms (Ashar et al, 2017;De la Fuente-Fernández et al, 2001;Ellingsen et al, 2013;Fields, 2004;Lidstone et al, 2005;Mayberg et al, 2002;Oken et al, 2008;Petrovic et al, 2002;Scott et al, 2007Scott et al, , 2008, another central hypothesis is that traits related to behavioral activation and reward responsiveness may be a positive predictor of placebo responsivity (De Pascalis & Scacchia, 2019;Schweinhardt et al, 2009). Conversely, behavioral inhibition has been linked to anxiety (Carver & White, 1994), and thus may be negatively associated with placebo improvement (Broelz et al, 2019).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Second, in line with previous findings suggesting that placebo improvement is underpinned by brain circuitry supporting reward and valuation mechanisms (Ashar et al, 2017;De la Fuente-Fernández et al, 2001;Ellingsen et al, 2013;Fields, 2004;Lidstone et al, 2005;Mayberg et al, 2002;Oken et al, 2008;Petrovic et al, 2002;Scott et al, 2007Scott et al, , 2008, another central hypothesis is that traits related to behavioral activation and reward responsiveness may be a positive predictor of placebo responsivity (De Pascalis & Scacchia, 2019;Schweinhardt et al, 2009). Conversely, behavioral inhibition has been linked to anxiety (Carver & White, 1994), and thus may be negatively associated with placebo improvement (Broelz et al, 2019).…”
Section: Introductionsupporting
confidence: 64%
“…Conversely, more pessimistic people may react more saliently to information about adverse outcomes and side effects, which in turn may contribute to nocebo effects. Trait anxiety, which is sometimes negatively associated with optimism (Scheier et al, 1994), and related to negative expectancy bias (Cabeleira et al, 2014) has been suggested as a negative predictor of placebo responsiveness (Broelz et al, 2019;Horing et al, 2014;Morton et al, 2009;. Similarly, neuroticism , pain catastrophizing (Sullivan et al, 2008), fear of pain (Corsi & Colloca, 2017;Lyby et al, 2010) have been linked to placebo effects as a negative predictor.…”
Section: Introductionmentioning
confidence: 99%
“…Participants completed a set of questionnaires (Table 1) to assess psychological traits that have previously been linked to placebo responsiveness (Broelz et al., 2019; Corsi & Colloca, 2017; Lyby et al., 2010; Zhou et al., 2019). Questionnaires were completed between the familiarization with the CPT and the test sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the psychobiological model of endurance performance posits that interventions designed to reduce perceptual exertion and/or enhance motivation may improve exercise tolerance [70,71]. Indeed, placebos have been observed to increase frontal alpha asymmetry and associated positive affect appraisal of effort perception, when described as ergogenic aids [72]. It is also plausible that perceptual exertion and/or motivation may share an inverse relationship [73], though subjective motivation was not directly assessed here.…”
Section: Discussionmentioning
confidence: 99%